Financial Technology and Financial Inclusion on MSME:Mixed-Method Research Approach - Wati, Lela Nurlaela; Isprihayadi, Heri; Nisa, Khoirun; Lutfi, Mohamad; Suprapta, Imam (Universitas Bina Sarana Informatika, 2020)
This study aims to examine the role of financial technology in increasing financial inclusion in Micro, Small, and Medium Enterprises. This research uses mixed-method research with sequential mixed methods especially sequential explanatory strategy. In the first phase, 116 questionnaires were given to respondents as many as 116 MSMEs then conducted interviews with respondents and related parties in depth. Empirical evidence shows that the role of Financial Technology has a positive and significant effect on Financial Inclusion. These results indicate that fintech can increase financial inclusion. Based on interviews, fintech products that are often used by MSMEs are third-party payment systems and Peer-to-Peer (P2P) type of payment systems. Examples of platforms that are often used by MSMEs are Go food, Gopay, Grab food, OVO, JakOne, M-Banking, and SMS Banking. For the Crowdfunding fintech type, it has not been implemented by many MSMEs. The large number of MSME entrepreneurs who have used fintech products in their businesses shows that MSME entrepreneurs have used financial services in the form of savings accounts so that it has an impact on increasing financial inclusion. Suggestions from the results of this study are the Government needs to conduct regular training on the use of financial technology to MSME actors, there are strong synergy and cooperation in developing a fintech system to improve the digital economic system at MSMEs. Regulations need to be updated with the development of innovations.